(untitled) (Research, Society and Development, 2022)
Objective: To assess the perception of risk for sexually transmitted infections in the elderly. Method: This is a cross-sectional study, descriptive and exploratory, with a quantitative approach to data developed in Community Centers for the Elderly (CCI) in the city of Caxias-MA, 220 participants were included in the research. There was the application of a semi-structured questionnaire in the form of an interview. Results: About 72.3% of the elderly were female, with a mean age of 71.44 years, widowed (45.5%); who have an affective partner (48.6%) who are sexually active (31%); who were satisfied with penetrative sex (26%); where 41.8% did not use condoms although 87.3% do not consider themselves at risk of contracting any STI. Conclusion: The sexual behavior of the elderly makes the elderly vulnerable, in the evidence of deficient knowledge about sexually transmitted infections (STIs), as well as unsafe sexual practice, making it necessary to create awareness strategies to promote healthy aging and overcoming prejudices existing.